ENDOMETRIOSIS-RELATED HOSPITALIZATIONS IN SOUTHEASTERN BRAZIL: AN ANALYSIS OF RACIAL DISPARITIES, AGE DISTRIBUTION, AND HEALTH EQUITY CHALLENGES. (REMUNOM, 2026)
Endometriosis is a chronic inflammatory pathology characterized by the presence of endometrial-like tissue outside the uterus, affecting pelvic and abdominal organs, and potentially leading to severe pain and infertility. This study aimed to analyze the landscape of hospitalizations for endometriosis in Southeastern Brazil between 2015 and 2024, investigating morbidity and mortality indicators, sociodemographic distribution, and the financial impact on the Unified Health System (SUS). An ecological, descriptive, and quantitative study was conducted using secondary data from SIH/DATASUS. The results revealed 53,105 hospitalizations, primarily concentrated in the states of São Paulo and Minas Gerais. The predominant age group was 30 to 49 years, highlighting delayed diagnosis until late reproductive stages. Although the overall mortality rate was low (0.15), a higher proportional lethality was observed among Black women (0.11%) compared to Pardo and White women, suggesting structural barriers in access to care and underdiagnosis. The total cost of hospitalizations exceeded R$ 32.5 million, reflecting the high complexity of cases reaching the hospital network. It is concluded that endometriosis in Southeastern Brazil is marked by ethnic-racial inequalities and a significant economic burden, necessitating public policies that strengthen early diagnosis and equity in women’s healthcare within the SUS.